Promoting collective security in Africa : the roles and responsibilities of the United Nations, African states, institutions, and western powers - Hailu, Solomon (Lanham, Md. : University Press of America, 2012)
"In principle, collective security is designed on a common understanding that peace and security is indivisible in which the load of order-keeping should be shared among all members of the collective security institution. The League of Nations and its heir, the United Nations, were created to achieve international security through collective measures; however, both institutions suffered from member countries' lack of necessary political will and resource commitment to make the collective security system work under different circumstances. This problem has been largely evident in addressing security problems in developing regions, particularly in Africa. The western powers (U.S., Britain, France) have less interest in sharing responsibility to enforce collective security system in Africa. Western nations have clearly elevated their national security imperatives to a higher level of importance over their obligation to the indivisibility of peace and collective security. Under such circumstance, there seems to be no alternative but that collective security should rely heavily on Africans themselves under the auspices of the newly established African Union (AU). African Union has undergone structural, doctrinal, and institutional changes to better handle security problems in the continent. Obviously young and weakly developed, AU regional security capacity proved that it is incapable of resolving the diverse and complex nature of conflict by itself. The widespread conflict in Africa has indeed pushed AU to over-commit itself beyond its capacity. Therefore, it will be necessary in the future for the AU to seek more support for collective security form the UN, Western powers, African regional security alliances and so-called African anchor states such as South Africa and Nigeria."--
Introduction -- The origin of collective security -- The UN collective security system -- International dimensions of conflict in post-colonial Africa -- Collective security system and peacekeeping in Africa -- African Union and challenges to peacekeeping -- African Union and African Sub-Regions' Role in Peacekeeping -- The UN and African regional bodies in peacekeeping -- South Africa's remission to the international system -- South Africa's peacekeeping role in Africa: push and pull factors -- Lesotho crisis and South Africa's intervention: what kind of peacekeeping? -- Nigeria and South Africa in peace support operation in Africa.
Includes bibliographical references (pages 133-151) and index.
Keywords: United Nations; African Union; African Union; United Nations; Security, International -- Africa; National security -- Africa; National security; Security, International; Africa